2002
DOI: 10.1093/oxfordjournals.molbev.a003984
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Amplification and Reorganization of Resistance Genes During Recent Arabidopsis thaliana Evolution

Abstract: The NBS-LRR (nucleotide-binding site plus leucine-rich repeat) genes represent the major class of disease resistance genes in flowering plants and comprise 166 genes in the ecotype Col-0 of Arabidopsis thaliana. NBS-LRR genes are organized in single-gene loci, clusters, and superclusters. Phylogenetic analysis reveals nine monophyletic clades and a few phylogenetic orphans. Most clusters contain only genes from the same phylogenetic lineage, reflecting their origin from the exchange of sequence blocks as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(193 citation statements)
references
References 35 publications
8
180
3
1
Order By: Relevance
“…For the Rx/Gpa2 cluster, a chromosome translocation/ inversion breakpoint dispersed the R-gene homologs and associated markers in other genera relative to potato. Others have observed the genomic distribution of R genes as a somewhat random phenomenon (Leister et al 1998;Pan et al 2000a;Richly et al 2002), but it has been since shown in Arabidopsis that R-gene locations are consistent with the rearrangements of their chromosomal context (Baumgarten et al 2003). In the Solanaceae, 22 genome rearrangements distinguish tomato and pepper (Livingstone et al 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Rx/Gpa2 cluster, a chromosome translocation/ inversion breakpoint dispersed the R-gene homologs and associated markers in other genera relative to potato. Others have observed the genomic distribution of R genes as a somewhat random phenomenon (Leister et al 1998;Pan et al 2000a;Richly et al 2002), but it has been since shown in Arabidopsis that R-gene locations are consistent with the rearrangements of their chromosomal context (Baumgarten et al 2003). In the Solanaceae, 22 genome rearrangements distinguish tomato and pepper (Livingstone et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The first predicts rapid rearrangement of R-gene distribution during genome evolution, yielding poor conservation of R-gene locations (Leister et al 1998;Richly et al 2002;Meyers et al 2003). Indeed, in monocots, extensive loss of genomewide R-gene colinearity has been attributed to frequent R-gene duplication and ectopic transposition (Gale and Devos 1998;Paterson et al 2003).…”
mentioning
confidence: 99%
“…In Populus, these clusters are distributed unevenly over the chromosomes and in clusters of clusters or "superclusters" of which three occur on chromosome XIX. Highly similar sequences in head-to-tail orientation suggest that intralocus recombination gave rise to the translocation of a sequence block (Richy et al 2002). The largest NBS-LRR gene supercluster on Populus chromosome XIX collocates with the resistance loci MER, R1, and RUS, conferring qualitative or quantitative resistance to Melampsora larici-populina (Lescot et al 2004;Jorge et al 2005;Bresson et al 2011).…”
Section: Lrr Genesmentioning
confidence: 99%
“…3). Plant R genes often occur in clusters, and genes within one cluster are mostly derived from a common ancestor (Richly et al 2002). Three distinct CC-NBS-LRR gene families were identified in the Mla locus within a 240-kb region (Wei et al 1999;Wei et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…R genes are usually organized in clusters, and genes within one cluster are mostly derived from a common ancestor (Richly et al 2002). The clustering feature can facilitate the expansion of R gene number and the generation of new R gene specificities through recombination and positive selection (Michelmore and Meyers 1998).…”
Section: Introductionmentioning
confidence: 99%